Correlation Analysis of Antioxidant Activities with Tannin, Total Flavonoid, and Total Phenolic Contents of Nutmeg (Myristica fragrans Houtt) Fruit Precipitated by Egg white - Irma Antasionasti; Olvie Syenni Datu; Utami Sasmita Lestari; Surya Sumantri Abdullah; Imam Jayanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The nutmeg (Myristica fragrans) flesh extract has a strong antioxidant activity. Therefore, M. fragrans flesh can be developed for functional drinks which are sources rich in antioxidants good for the prevention and treatment of diseases such as cancer and cardiovascular diseases. However, the tannins' content can cause a bitter and sour taste. Therefore, the tannins content should be reduced by the addition of egg white. The purpose of this study is to find out the comparison of antioxidant activity between a combination of M. fragrans flesh extract with various concentrations of egg white and to correlate its antioxidant activities with tannin, total flavonoid, and total phenolic contents. The antioxidant activities were conducted on M. fragrans flesh extract by using DPPH and ABTS radicals. Tannin, total flavonoid, and total phenolic contents from M. fragrans flesh extract were also tested. The M. fragrans flesh extracts without addition egg white have a strong antioxidant in scavenging the stable free radical ABTS (89.980±0.480 µg/mL) and intermediate antioxidant in scavenging the stable free radical DPPH (105.669±0.102 µg/mL). It is followed accordingly by tannin, total flavonoid, and total phenolic contents, namely 14.034±0.100 %w/w TAE, 26.929±0.129 %w/w QE, and 53.164±0.129 %w/w GAE, respectively. Correlation of tannin, total flavonoid, and total phenolic contents, which inhibited DPPH and ABTS radicals had R2 values of about 89.23-97.63%. It showed that antioxidant activity is strongly influenced by the tannin, total flavonoid, and total phenolic contents. Therefore, precipitation from the tannin-protein bond caused antioxidant activities were decreased.